Формування чеських поселень на Півдні України: чехи Північного Приазов’я (60-70 рр. ХІХ - початок ХХ ст.) - Курінна, М. (Народна творчість та етнографія, 2008)
Lately within the framework of our state's history and culture studies there is the increase of interest to the national minorities which live on territory of Ukraine. From data of the last census of population of 2001 year, the quantity of the Czech population in the demographic list of the ethnic groups of our country diminished almost on the third as compared to previous numbers, which is linked with assimilative processes, from one side, and with the re-emigration of part of the migrants to Czechia, from another side. Taking into account such statistics, the study of original culture of the Ukrainian Czechs is not simply important, but is the urgent task of Ukrainian science, since the Czech cultural layer disappears quickly enough under the influence of different factors.